Efek Moderasi Risiko Pasar pada Pengaruh Kepemilikan Manajerial Terhadap Nilai Pasar Perusahaan Goto - T Fawazlul Rizqi; Aldi Akbar (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to examine the impact of managerial ownership on firm market value, with market risk as a moderating variable producing conditional effects. The research covers the period from Q2 2022 to Q3 2023 in GOTO companies. The methodology employed is Conditional Process Analysis (CPA) by Andrew F. Hayes. Data were sourced from audited annual reports of the companies. The findings reveal that managerial ownership significantly negatively affects firm market value. However, when moderated by market risk, this relationship turns significantly positive across all levels of market risk (low, moderate, high), indicating that market risk effectively moderates the relationship between managerial ownership and firm market value.